VARIABILITY OF SEA SURFACE TEMPERATURE AT FISHERIES MANAGEMENT AREA 715 IN INDONESIA AND ITS RELATION TO THE MONSOON, ENSO AND FISHERY PRODUCTION - Suniada, Komang Iwan (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2020)
Sea surface temperature (SST) is one of the important oceanographic and climatemparameters. Its variability and anomaliesmoften influence the environment and organisms, both in the oceansand on land. This study aims to identifythe variability of SST and help the fisheries community to understand how climate phenomena such as ENSOand monsoonal phases (represented by wind speed) are related to SST and fishery production in Fisheries Management Area (FMA)715.SST was measured at Parimo, which represents conditionsinthe western partof the areainside Tomini Bay,and at Bitung, which represents SST in the open ocean,with a more exposuredgeographical position. SST wasderived from MODIS satellite imagery, downloaded from the ocean color database (https://oceancolor.gsfc.nasa.gov/) with a4 km spatial resolution, from January 2009 to December 2018. Wind speed data, historical El Niño or La Niña events,and fish production data were also used in the study. Pearson’s correlation (Walpole, 1993) was used to test the relationship between SST variability or anomaly and ENSO and monsoons. The results show that the SST characteristics and variability of the Parimo and Bitung watersare very different, although they bothliein the same FMA 715. SST in Parimo waters is warmer,but with lower variability than in Bitung waters. SST in Parimo has a lowcorrelation with ENSO (r=0.06, n=66), low correlation with wind speed (r=-0.29, n=120),with also a lowcorrelation between SST anomaly and ENSO (r=0.05, n=66). SST in Bitung has a higher, but inverse, correlation with ENSO (r=-0.53, n=66), highcorrelation with wind speed (r=-0.60, n=119), with also a high correlation between SST anomaly and ENSO (r=-0.74, n=66). Unlike in other parts of Indonesia, fishery production in Parimo,or the western part inside Tomini Bay,is not affected by ENSO events